FORMATION OF THE SYSTEM OF FINANCING ENVIRONMENTAL ACTIVITIES IN RUSSIA - Burmatova, Olga; Sumskaya, Tatiana (Journal of European Economy, 2017)
The paper is devoted to the problems of formation of the financial mechanism of environmental protection in the framework of local production systems. The authors identified main sources of costs for environmental purposes and analyzed the trend of reducing the fiscal costs of environmental protection. Particular emphasis is placed on the legal aspects of the use of payments for negative impact on the environment, including the abandonment of the use of funds to the budget as the price of a negative impact on the environment. The importance of environmental funds in the financing of environmental activities is shown, the importance of programmer – oriented approach to solving environmental problems is marked. The possible elements of the financial mechanism for the implementation of environmental protection measures are proposed. The main difficulties including stimulating effect in the economic mechanism of nature conservation and environmental protection are marked.